Analisis Implementasi Akuntansi Sektor Publik Dalam Sistem Keuangan Perusahaan Daerah Panca Karya Di Kota Ambon - Andriany, Dynne (Politeknik Negeri Ambon, 2025)
This research aims to analyze the implementation of public sector accounting in the financial system at the Panca Karya Regional Company, Ambon City. This research focuses on the application of accounting standards, the challenges faced, and the impact on financial performance and corporate accountability. The method used is a qualitative method through structured interviews by using a questionnaire. This research shows that the Panca Karya regional company has good accountability because it uses external parties to check its financial reports even though there are challenges regarding HR competency, asset management, and information technology. Therefore, optimization efforts can be made through training or investment in technology so that regional companies can apply SAK ETAP properly and correctly in their financial reports to provide economic and non-financial information to necessary parties for decision-making.